(3GdOQI GdSfjI aj ebJVi GdeYGde GdSfjIs - (3GHf GUHZ , eMeO Hf YjSi Hf eMeO Hf GUHZ Hf GdefGUa GdGROj, CHh YHO Gddg,J (B620 (3g` s
(3ChdgG (B:s
(3GdMeO ddg dg GdMeO Cgd GdKfGA QHfG hGdeLO Ld LdGd Gdedc GdYXje GdNGdb GdebJOQ GdcQje s
(3BNQgG (B:s
(3ai CKfGA fXe Yf GdSfI GdJGSYI ef gLQI GdfHi Udi Gddg Ydjg hSde s
(3eNWhWI ai YOI afhf ef LedJgG Gdabg hGdSjQIs
(3hgj fXe ai fMh SHYI BdGa HjJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B322 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B107s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B740s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs